Importance of glycosidases in mammalian glycoprotein biosynthesis - Herscovics, Annette (BBA - General Subjects, 1999)
Processing glycosidases play an important role in N-glycan biosynthesis in mammalian cells by trimming Glc 3Man 9GlcNAc 2 and thus providing the substrates for the formation of complex and hybrid structures by Golgi glycosyltransferases. Processing glycosidases also play a role in the folding of newly formed glycoproteins and in endoplasmic reticulum quality control. The properties and molecular nature of mammalian processing glycosidases are described in this review. Membrane-bound α-glucosidase I and soluble α-glucosidase II of the endoplasmic reticulum remove the α1,2-glucose and α1,3-glucose residues, respectively, beginning immediately following transfer of Glc 3Man 9GlcNAc 2 to nascent polypeptides. The α-glucosidases participate in glycoprotein folding mediated by calnexin and calreticulin by forming the monoglucosylated high mannose oligosaccharides required for the interaction with the chaperones. In some mammalian cells, Golgi endo α-mannosidase provides an alternative pathway for removal of glucose residues. Removal of α1,2-linked mannose residues begins in the endoplasmic reticulum where trimming of mannose residues in the endoplasmic reticulum has been implicated in the targeting of malfolded glycoproteins for degradation. Removal of mannose residues continues in the Golgi with the action of α1,2-mannosidases IA and IB that can form Man 5GlcNAc 2 and of α-mannosidase II that removes the α1,3- and α1,6-linked mannose from GlcNAcMan 5GlcNAc 2 to form GlcNAcMan 3GlcNAc 2. These membrane-bound Golgi enzymes have been cloned and shown to have very distinct patterns of tissue-specific expression. There are also broad specificity α-mannosidases that can trim Man 4–9GlcNAc 2 to Man 3GlcNAc 2, and provide an alternative pathway toward complex oligosaccharide formation. Cloning of the remaining α-mannosidases will be required to evaluate their specific functions in glycoprotein maturation.